1994
DOI: 10.1002/per.2410080305
|View full text |Cite
|
Sign up to set email alerts
|

War and children's aggressive and prosocial behaviour

Abstract: The aim of this study was to investigate whether, and how, extreme environmental influence, such as a war situation, can affect the development of children's aggressive and prosocial behaviour. A combined longitudinal–cross‐sectional design was used in the study. Subjects were preschool children whose behaviour was rated on the Children's Aggressive and Prosocial Behaviour Rating Scale (Žužul, Keresteš and Vlahović‐štetić, 1990) by their teachers. At the beginning of 1991 (before the war in Croatia started) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…A longitudinal study, conducted in the early 1990s among 5-and 6-year-old children in Zagreb, Croatia, revealed that prosocial behaviors rated by teachers, such as sharing sweets and toys or feeling sorry for other children in need, were significantly increased after the experience of war, whereas aggressive behavior remained the same (Raboteg-Š aric, Ž užul, & Keresteš, 1994). This study controlled for developmental effects.…”
Section: Helping Beyond the Immediate Situation Of Sufferingmentioning
confidence: 88%
See 3 more Smart Citations
“…A longitudinal study, conducted in the early 1990s among 5-and 6-year-old children in Zagreb, Croatia, revealed that prosocial behaviors rated by teachers, such as sharing sweets and toys or feeling sorry for other children in need, were significantly increased after the experience of war, whereas aggressive behavior remained the same (Raboteg-Š aric, Ž užul, & Keresteš, 1994). This study controlled for developmental effects.…”
Section: Helping Beyond the Immediate Situation Of Sufferingmentioning
confidence: 88%
“…This is suggested in the studies of soldiers in war (Blake, 1978;Rachman, 1979), Holocaust survivors (Kahana et al, 1985), individuals present during a terrorist attack (Kleinman, 1989), siblings of disabled children (Hannah & Midlarsky, 2005;McHale & Gamble, 1989), and survivors of natural disasters (Kaniasty & Norris, 1995b). Moreover, individuals who suffer and depend on help encounter altruistic role models (e.g., during war: Raboteg-Š aric et al, 1994;in hospitals: Seagle et al, 2002), and the reciprocity norm of helping can explain high levels of mutual support in times of human-made and natural disasters (e.g., in concentration camps: Kahana et al, 1985;during natural disasters: Kaniasty & Norris, 1995b).…”
Section: Motivational Processes and Volitional Factorsmentioning
confidence: 91%
See 2 more Smart Citations
“…A study among Croatian preschoolers compared physical and verbal aggression before and during the major war and atrocities, and found no changes in either type of aggression during the war [Raboteg-Sˇaric et al, 1994]. However, 10 years later in post-war conditions, the children and adolescents exposed to severe war trauma in preschool age showed higher level of aggressive behavior than less exposed [Kerestesˇ, 2006].…”
Section: Introductionmentioning
confidence: 97%